Pengaruh Pengaruh Literasi Asuransi dan Promosi Terhadap Minat Berasuransi Syariah Dengan Kepercayaan Sebagai Variabel Mediasi - Ramdan, Taufik; Izzani Ulfi; Andina Dwi Iryanti (Universitas Islam Lamongan, 2026)
Abstract: This study aims to examine the influence of insurance literacy and promotion on millennials’ interest in Islamic insurance, with trust as a mediating variable. Using a quantitative approach and the SEM-PLS method, data were collected from 162 millennial respondents in Jabodetabek. The findings show that insurance literacy and promotion simultaneously and significantly affect trust. Individually, both also have significant effects, indicating that understanding and effective promotion strategies foster trust in Islamic insurance products. Furthermore, literacy, promotion, and trust both simultaneously and individually significantly influence interest, highlighting the role of knowledge, marketing communication, and confidence in increasing millennial interest in Islamic insurance. The indirect effect analysis reveals that trust significantly mediates the relationship between promotion and interest, but not between literacy and interest. Thus, promotion plays a crucial role in influencing interest both directly and through trust. These findings suggest that Islamic insurance companies should develop educational and trust-building promotional strategies to enhance millennial engagement with sharia-compliant insurance products. Keywords: Insurance Literacy, Promotion, Trust, Interest, Islamic Insurance